Bacterial and Fungal Contamination of Tools Used in Women Beauty Salons in Aqqala, Iran - Abolfazl Amini; Ali Zafarzadeh; Halimeh Mohammadi (International Journal of Environmental Health Engineering, 2025)
Aim: Women beauty salons are considered as public places that can contribute to the transmission of many diseases. The present study aimed to assess the sanitary status of women beauty salons in Aqqala City in 2018. Methods: The present descriptive-analytical study was conducted on a total of 480 samples of applied equipment in women beauty salons such as combs, scissors, tweezers, and aprons. The samples were selected through census, and sampling was done by sterile swab, which was wetted with trypticase soy broth, from the external surface of instruments, and they were then inoculated into differential selective culture media. Isolated colonies were identified by standard biochemical tests. Results: Two hundred and two (42.08%) out of 480 cultured samples were positive in terms of microbial contamination. The most bacterial and fungal contamination was reported in combs (42.5%) and aprons (31.66%), respectively. There was a significant relationship between the amount of microbial and fungal contamination (P ≤ 0.005). The highest levels of bacterial and fungal contamination belonged to Staphylococcus aureus (17.5%) and Candida albicans (7.5%). Conclusion: Given the high level of contamination in the present study, the attention should be paid to effective methods of sanitation and disinfection of hairdressing equipment, and such places should be monitored in a fully organized way.